PENERAPAN MODEL PEMBELAJARAN SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 1 YEHKUNING - PRIANTINI, DEWA AYU MADE MANU OKTA (Widya Accarya, 2018)
ABSTRACTÂ Â Â Â Â Â Â  Education is one of manifestation of dynamic human culture and sarad of culture. Therefore, the development or change in education is something that must happen in line with the changing culture of life. The purpose of this education will be achieved well if the chosen teaching method or model can be applied seriously and the students more easily understand the lesson material presented, the students are more passionate, and happy to learn. Among the various methods and models available, researchers chose the "Snowball Throwing Learning Model" for use in classroom action research. The application of the snowball throwing learning model has succeeded in improving the IPS learning outcomes in the material of appreciating the role of warriors and the public in proclaiming and maintaining the independence of Indonesian V students of second semester at No.1 Yehkuning Elementary School year 2017/2018. This can be seen from the percentage of IPS student learning outcomes of class V in cycle I increased 21% in cycle II. Thus, the application of snowball throwing learning has succeeded in improving the IPS learning outcomes in the material appreciate the role of warriors and the public in proclaiming and maintaining Indonesian independence of second semester V students in No 1 Yehkuning Primary School year 2017/2018Â Keywords: Snowball Throwing, Result Study, Social subjectÂ ABSTRAKPendidikan adalah salah satu bentuk wujud dari kebudayaan manusia yang dinamis dan sarad akan kebudayaan. Oleh karena itu, perkembangan atau perubahan dalam pendidikan adalah hal yang harus terjadi sejalan dengan perubahanÂ  budaya kehidupan. Tujuan pendidikan ini akan dapat tercapai dengan baik apabila metode atau model mengajar yang dipilih dapat diterapkan dengan sungguh-sungguh dan siswa lebih mudah memahami materi pelajaran yang disajikan, siswa lebih bergairah, serta senang dalam belajar. Di antara berbagai metode dan model yang ada, peneliti memilih â??Model Pembelajaran Snowball Throwingâ? untuk digunakan dalam penelitian tindakan kelas. Penerapan model pembelajaran snowball throwing telah berhasil meningkatkan hasil belajar IPS pada materi menghargai peranan tokoh pejuang dan masyarakat dalam memproklamasikan dan mempertahankan kemerdekaan Indonesia siswa kelas V semester II di Sekolah Dasar No.1 Yehkuning tahun pelajaran 2017/2018. Hal ini dapat dilihat dari persentase hasil belajar IPS siswa kelas V pada siklus I meningkat 21 % pada siklus II. Dengan demikian, penerapan pembelajaran snowball throwing telah berhasil meningkatkan hasil belajar IPS pada materi menghargai peranan tokoh pejuang dan masyarakat dalam memproklamasikan dan mempertahankan kemerdekaan Indonesia siswa kelas V semester II di Sekolah Dasar No No.1 Yehkuning tahun pelajaran 2017/2018Â Kata kunci : Model Pembelajaran Snowball Throwing, Hasil Belajar IPS